Recent advances in sustainable catalytic production of 5-methyl-2-pyrrolidones from bio-derived levulinate. (15th February 2023) - Jiang, Yiyuan; Li, Zao; Li, Yuncong; Chen, Long; Zhang, Heng; Li, Hu; Yang, Song
Highlights: Sustainable catalytic production of 5MPs from bio-based feedstocks shows promise. Protocols for preparing 5MPs by reductive amination are systematically summarized. Activity of state-of-the-art metal-based catalysts are compared and emphasized. Reaction pathways/mechanism and catalysts stability are systematically analyzed. Challenges and trends for upgrading biomass to high-value chemicals are discussed. Abstract: At present, massive and renewable biomass energy is being deemed an emerging potential energy reserve. Given the non-renewable fossil raw materials with pollution-related problems, biomass has attached great importance to serving as a significant substitute for production of various functional chemicals and materials in sustainable development. Levulinic acid (LA) and its esters, derived from the hydrolysis of biomass, are pivotal platform molecules endowed with special structures that can be converted into a variety of attractive chemicals such as 5-methyl-2-pyrrolidones (5MPs) by reductive amination. 5MPs are playing an important role in our daily life such as pharmaceutical, dye, and other industries. In this review, the latest advances in the sustainable catalytic reductive amination of LA and its ester with different nitrogen and hydrogen sources to prepare 5MPs over noble metal and non-noble metal catalysts are systematically introduced. Emphasis is placed on the discussion of effective catalyst-free/ metal catalyst catalytic conversion process in terms of producing 5MPs. Although the reaction conditions of various catalytic systems are found to be different, the relevant catalytic parameters such as temperature, solvent, and time are compared as far as possible. In addition, the corresponding reaction mechanism, catalyst efficiency and reusability, and reactive modes including the continuous-flow production process are also discussed. Last but not least, based on the previous results depicted in this review, the guidance for the future development of the sustainable catalytic system with great potential to promote the utilization of biomass energy and the synthesis of high-value chemicals has been prospected.